2021
DOI: 10.3390/nu13051511
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Topical Vitamin D, Sunshine, and UVB Phototherapy Safely Control Psoriasis in Patients with Normal Pretreatment Serum 25-Hydroxyvitamin D Concentrations: A Literature Review and Discussion of Health Implications

Abstract: Vitamin D, sunshine and UVB phototherapy were first reported in the early 1900s to control psoriasis, cure rickets and cure tuberculosis (TB). Vitamin D also controlled asthma and rheumatoid arthritis with intakes ranging from 60,000 to 600,000 International Units (IU)/day. In the 1980s, interest in treating psoriasis with vitamin D rekindled. Since 1985 four different oral forms of vitamin D (D2, D3, 1-hydroxyvitaminD3 (1(OH)D3) and 1,25-dihydroxyvitaminD3 (calcitriol)) and several topical formulations have b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 298 publications
(635 reference statements)
1
3
0
Order By: Relevance
“…Our study showed that after three months of vitamin D supplementation, as many as 80% of patients had achieved the optimal vitamin D concentrations and this effect correlated with clinical improvement of skin lesions, as judged by the decreased PASI scores. These results are in accordance with previous findings which were systematized in a very recent review [ 25 ]. Such a clinical improvement was expected, as the relationship between vitamin D deficiency and psoriasis is well established [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our study showed that after three months of vitamin D supplementation, as many as 80% of patients had achieved the optimal vitamin D concentrations and this effect correlated with clinical improvement of skin lesions, as judged by the decreased PASI scores. These results are in accordance with previous findings which were systematized in a very recent review [ 25 ]. Such a clinical improvement was expected, as the relationship between vitamin D deficiency and psoriasis is well established [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…This could explain the observation that serum 25(OH)D was inversely correlated with presence of PsA [ 95 ], as well as plasma C-reactive protein level among patients with PsA [ 96 ]. Moreover, some reports have shown marked clinical improvement in patients with psoriasis who received up to 50,000 IUs per day of oral vitamin D 3 [ 97 , 98 , 99 ]. However, the benefit of lower doses of up to 4200 IUs per day or equivalent of vitamin D supplements for the treatment of psoriasis is still unverified based on the results of a few clinical trials [ 100 ].…”
Section: Evidence On Vitamin D For Prevention and Treatment Of Rheumatic Diseasesmentioning
confidence: 99%
“…70 , 72–74 Topical vitamin D analogues like calcipotriol and calcitriol have long been a part of standard dermatological treatment for psoriasis, but the efficacy of oral vitamin D supplementation remains unclear. 75 Although numerous studies have shown vitamin D as a popular supplement for patients, 3 , 4 , 6 clinical trial data have shown conflicting evidence, with the most recent NPF guidelines written in 2018 stating that oral vitamin D was not recommended for psoriasis patients. 7 More recent studies and meta-analyses have found similar outcomes—results continue to be mixed on efficacy, though few adverse effects tend to be noted in treatment groups.…”
Section: Resultsmentioning
confidence: 99%